La pena de muerte como máximo castigo y su impacto en la sociedad contemporánea. - Cuesta Márquez, Lianet; Sarie Añazco, Ángel Andrés (Universidad Técnica de Machala, 2020)
The main objective of this research is to analyze the law of the death penalty as the protagonist of the moral uncertainty of Human Rights and its conceptions, by comparing the legal systems of the different States. In addition, the current regulations in the country are established with respect to the same and the social opinion found in the city of Machala, Ecuador.To satisfy this purpose, a qualitative-quantitative methodology has been used to inquire about the subject in question. Similarly, techniques such as interviews, surveys and documentary observation have been used. The current global trend with regard to capital punishment is its abolition, which is why each legal system is expected to achieve this goal. In Ecuador, the death penalty was abolished more than a hundred years ago and its application is incompatible with its constitutional text and with the international treaties it has signed. However, as a result of the study, it was found that not all members of Ecuadorian society agree with this position. At the national level, it is concluded that this is due to the criminal populism that many legislators use in their political speeches, to the weak system of social rehabilitation in the country and the disappointment of citizens before the declared sentences.
El objetivo principal de la presente investigación es analizar la ley de la pena de muerte como protagonista de la incertidumbre moral de los Derechos Humanos y sus concepciones, mediante la comparación de los sistemas jurídicos de los diferentes Estados. Además, se establece la normativa vigente en el país con respecto a la misma y la opinión social encontrada en la ciudad de Machala, Ecuador. Para satisfacer dicho propósito se ha utilizado una metodología cualitativa-cuantitativa para indagar sobre el tema en cuestión. Del mismo modo se ha recurrido a técnicas como entrevistas, encuestas y a la observación documental. La tendencia mundial actual con respecto a la pena capital es su abolición, por lo que se espera que cada sistema jurídico logre dicho cometido. En Ecuador, la pena de muerte se abolió hace más de cien años y su aplicación es incompatible con su texto constitucional y con los tratados internacionales que ha firmado. Sin embargo, como resultado del estudio se obtuvo que no todos los miembros de la sociedad ecuatoriana concuerdan con esta postura. A nivel nacional, se concluye que esto se debe al populismo penal del que se valen muchos legisladores en sus discursos políticos, al débil sistema de rehabilitación social en el país y la decepción de los ciudadanos ante las sentencias declaradas
Keywords: PENA DE MUERTE; CASTIGO; JURÍDICO; LEYES